Additive Fabrication of 3D Anepectic Structures - Silva, Daniela Barras Nunes Serra e (2022)
This work focuses on the design and manufacture (by additive fabrication) of 3D anepectic structures. These anepectic structures have two rare characteristics: they exhibit negative values of Poisson’s ratio and of coefficient of thermal expansion (CTE). Negative values of CTE are activated by the combination of two different materials, in which both have positive values of CTE. This type of structure is useful in applications such as in the biomedical and aerospace fields, where it is important to have a mechanical response to a thermal stimulus. Ten samples were studied and subjected to thermo-mechanical tests: five single material samples (four of Nylon and one of CPE+) and five dual material samples (four of Nylon-PVA and one of Nylon-CPE+). All samples were subjected to tensile tests in which the most negative value of Poisson’s Ratio achieved in this work was of -1.103. All samples were subjected to thermal tests, in which they were submerged in silicone oil (Baysilone M350) and, then, subjected to a heating process. In this type of test, the most negative value of CTE was of -812× 106 /º at 120ºC. Palavras-chave: Impressão 3D, Auxética, Expansão térmica negativa, Anepéctica, Coeficiente de Poisson negativo.